Pakistan's home-grown terrorism threat : war beyond 2014 - Abdul Basit (2014)
The upsurge in terrorist violence in Pakistan this month indicates the trajectory of its home-grown terrorism by Islamist insurgents well beyond 2014. Besides a strong military response to win the fight against militants, the political leadership must take ownership of the war and demonstrate strong political will.